Professional Development of English Teachers at a State Islamic Senior High School in Palembang - Rizki Fadhliyah; Soni Mirizon; Ismail Petrus (Pusat Pelatihan, Riset, dan Pembelajaran Bahasa, 2020)
The objectives of this study were to investigate teachers’ professional development, the obstacles faced by the teachers, teachers’ efforts to resolve the obstacles, and school support for the teachers in continuing professional development. To reveal the phenomenon, qualitative case study design was used. This study combined observation, questionnaires, and interviews in data collection. English teachers, vice-principal of the curriculum, teachers who taught other subjects, and students who had been taught by the English teachers were the participants of this study. Findings revealed that English teachers’ professional development was good. The results also revealed that teachers’ scientific publications were in the poor category. Innovative works for both English teachers were in the average category. Lack of time and information were the obstacles faced by the English teachers in continuing professional development. Teachers attempted to resolve the obstacles by looking for information needed through the internet. They also had discussions with other teachers to gain information for their knowledge. The school frequently conducted some programs related to teachers’ professional development and allowed them to attend professional development activities held by other institutions.